Visual Analysis of Research Progress on the Impact of Cadmium Stress on Horticultural Plants over 25 Years - Zhouli Liu; Benyang Hu; Yi Zhao; Shuyan Zhang; Xiangbo Duan; Hengyu Liu; Luyang Meng (Horticulturae)
In recent years, there has been a significant growth in scholarly attention to the effects of Cd stress on horticultural plants, as reflected by the abundance of research articles on this issue in academic publications. Therefore, it is necessary to conduct a review of current research and provide a comprehensive perspective to quickly grasp the latest developments and future trends in the research field of “horticultural plants-Cd responses”. By utilizing a visualizing bibliometric analysis software CiteSpace, this study integrated and analyzed a total of 4318 relevant research records—2311 from the Web of Science (WOS) database and 2007 from the China National Knowledge Infrastructure (CNKI) database—related to “horticultural plants-Cd responses”, covering the period from 1999 to 2024. A visual analysis was conducted in the form of knowledge mappings, including the current research status of “horticultural plants-Cd responses”, as well as the differences in publications’ temporal distribution, spatial distribution (cooperation networks) and intellectual base between China and foreign countries, precisely uncovering the core aspects of research topics related to the field. The results indicated the following: (1) Scientific research on “horticultural plants-Cd responses” has experienced a significant increase in publication volume and has entered a phase of rapid development. Globally, there has been an annual average increase of 217 articles in the WOS since 2019, while in China, the annual average increase has been 134 articles in the CNKI since 2015. (2) China is the most productive country in terms of publication volume (1165 articles, 52.79%), engaging in active partnerships with other countries worldwide. Chinese scholars (Lin L. and Liao M.) are leading researchers in both domestic and international research fields of “horticultural plants-Cd responses”. The network of collaborations among authors and institutions in the WOS database seemed denser compared to that in the CNKI database. (3) International research hotspots have focused on accumulation, tolerance and oxidative stress, while domestically, the focus has been on antioxidant enzymes, growth and seed germination. Phytoremediation, subcellular distribution and the transcriptome are the world’s emerging topics, while in China, growth and physiological characteristics are still emerging topics. (4) In comparison, China exhibited a lagging development trend, which is reflected in the fact that it began to focus on gene expression and transcriptome research only after the global frontier shifted towards biochar and cadmium co-stress and yield response. Based on these, this study provides a systematic theoretical basis for subsequent research on “horticultural plants-Cd responses”, aiding scholars in their efforts to understand the dynamic frontiers and address the challenges in this field.